Development of Eco-Responsible Thermal Comfort Designs for the Valorization of the Traditional Malagasy House - Miliarison Andrianiaina Josoa; Razafindrakoto Ny Riana Fanoina; RANAIVOSON Sahondra Lalao Olga; Randrianoelina Benjamin; Muhammad Ridwan; Koto-Te-Nyiwa Ngbolua; Robijaona Rahelivololoniaina Baholy (Budapest International Research and Critics University, 2022)
This study aims to provide any assistance in the design of a green thermal comfort solution that is aware of the current climate change and considers sustainable development. This concept is helpful to the environment and offers a possibility of popular use. The process results are reproducible to a maximum of eventuality in the thermal building field, but in this article, we discussed the cases of Malagasy thatched cottage with envelope in mud and roof in thatch and the case of an ordinary house of the popular Malagasy mass, with fired clay brick envelope, cement coating, galvanized corrugated iron roof. The approach is as follows: locate the study area, analyze the scenarios of ecological thermal solutions, carry out the heat balances according to the scenarios, and classify the optimal solution. To do this, METEONORM is used for geographical location, the heat balance is carried out using the THERMEXCEL tool, and the multi-criteria analysis is made by the PROMETHEE tool in the educational version.